Exploration of Women’s Experiences of Sexual Function after Female Genital Cosmetic Surgery: A Phenomenological Descriptive Study - Nezhad, Fatemeh T.; Jalali, Rostam; Karimi, Fozieh; Menati, Lida (Current Women's Health Reviews, 2023)
Background: Female genital cosmetic surgery (FGCS) consists of a set of design approaches to recover or strengthen the vulva. These cosmetic procedures are conducted to relieve functionality problems such as vaginal looseness and sexual dissatisfaction. The external genital tract is shaped cosmetically. Its results could be better judged through understanding the direct experience of women who underwent surgery. Therefore, this study aimed to explain the experiences of women regarding FGCS through phenomenological methods. Methods: In a phenomenological study with purposive sampling, semistructured in-depth interviews were conducted on women who experienced FGCS. Then, the interviews were entered into the Word software and were analyzed by the Colaizzi 7-step method. To ensure the correctness of the data, the Guba’s criteria were used. Data were analyzed using MAXQDA software version 10. Results: The results showed that 15 women aged between 23 and 49 years old and with a mean age of 34 years old, mostly married and housewives as well as with diploma educational levels, participated in the study. Three themes and eight subthemes were excluded from the analysis of participants’ interviews. Participants presented their experiences on their sexual function after FGCS as sexual satisfaction, high-quality life, and willingness for surgery. Conclusion: The studies showed those women’s experiences with FGCS were positive, resulting in sexual satisfaction and higher quality of life. Therefore, the assessment of women to perform cosmetic surgery should be prioritized, and the women should be supported to make a decision regarding such surgery.
Keywords: Qualitative research